Screening of different doses of lyophilized beetroot for their hematopoietic potential. - Sarfaraz , Sana; Ikram , Rahela; Munawwar, Rabia; Gul, Sabiha (International Journal of Endorsing Health Science Research, 2023)
Background: Beetroots are considered a vital source of nutrition and are usually incorporated into the daily diet to prevent different disease conditions. The therapeutic effect observed is due to the presence of active ingredients in the vegetables. The majority of our population, especially females, suffers from anemia due to malnutrition. The perseverance of this research was to explore the hematopoietic effects of lyophilized beetroot powder at different doses so they could be recommended as a nutritional supplement. Methodology: Albino rabbits weighing 1500-2000 gm of either gender were selected for the study and alienated into three sets. Set I was administered distilled water, whereas sets II and III were given lyophilized beetroot 500 mg/kg and 1000 mg/kg, correspondingly. For hematopoietic evaluation of blood, automated huma count plus was utilized. After adjusting according to their weights, lyophilized beetroot powder was suspended in distilled water and given at 500 mg/kg and 1000 mg/kg to rabbits. They were dosed once daily for two months. Results: The effects were verified before the dosing was scheduled and on the 30th day and 60th day of dosing. The outcomes presented a highly noteworthy increase (p<0.0001) in hemoglobin, erythrocyte count, hematocrit, leukocyte count, and thrombocytes by both doses. 500 mg/kg dose showed a more significant increase in leukocytes and thrombocyte count compared to 1000 mg/kg, whereas 1000 mg/kg showed a more substantial increase in erythrocytes and Hb as compared to 500 mg/kg at the conclusion of the study period. Conclusion: From the above, it can be concluded that beetroot possesses pronounced hematopoietic effects and might be beneficial as a non-pharmacological treatment for anemia and thrombocytopenia.